Empowering holistic learning experience through Project Outcome-based Learning (Po-BL): reflecting on a case study of Malaysian university undergraduate students - Omar, Muhd Khaizer (Primrose Hall Publishing Group, 2019)
The application of Project Outcome-based Learning (Po-BL) has been applied in teaching and learning environments for many years. Po-BL plays an important role in ensuring students learning effectiveness and frequency. Po-BL offers tangible invention as a result that is proof of student participation and which confirms student competency in the relevant subject-matter. However, it is often misinformed that not only can Po-BL transform student comprehension, in the context of the subject matter at hand, but also indirectly promotes student practical understanding which becomes the ultimate goal of the teaching and learning. This research argues that the existing accepted method of Po-BL, was not solely designed for the purpose of developing a product, but also encourages overall student learning experiences. In contemplating the issue, this research is a case study of 40 undergraduate students enrolled in STE3603 (Manipulative Skills III). This course takes 14 weeks (one semester) to complete. The students have undergone myriad Po-BL activities and participated in organizing an Innovation Showcase at the Faculty of Educational Studies, Universiti Putra Malaysia. As part of the showcase, students were able to exhibit their invention (Robot) by contesting in a RoboWars competition. The students who experienced multiple phases in the Po-BL activities were invited to be part of the research study by answering online qualitative open-ended questions via Jot Form. The questions were formulated in a broader sense to allow participants to reflect on their entire experiences from Po-BL activities. All responses were downloaded in an Excel Spreadsheet and analyzed using two different phases, both Word Cloud and thematic analysis with the color-coding technique. The themes that emerged from the study describe the entire learning outcomes from the Po-BL experiences, which guide future research to glean more understanding on what Po-BL potentially offers.